Electronic processes at solid surfaces - Ilisca, E
Includes bibliographical references.; The subject of surface physics has now grown to become an exciting interdisciplinary field of research with important practical applications.The purpose of this book is to provide a guided tour of some recent advances, key research issues and approaches in electronic processes at solid surfaces.Apart from a few structural studies, selected topics have been chosen to illustrate the dynamical response of the solid surface to external probes, with the main emphasis on electron transfer phenomena.